Asia del Pacífico ante Estados Unidos : un enfoque heterodoxo - Ramírez Bonilla, Juan José (Estudios Internacionales, 2004)
For most analysts, September 11 marks a drastic turn in the evolution of the international relations system: the North American interventions did not have an efficient opposition from the secondary powers and would have contributed to the unipolar consolidation of the international order. The present work offers a different interpretation: based on recent crucial events, it argues that “the global order” is marked by a contradictory situation. On the one hand, the US government is capable of imposing its interests globally, but this imposition is carried out at the cost of international crises; on the other hand, the international crises caused affect the interests of the regional powers, forcing them to oppose and dispute influence in their own geographical areas. Despite acrimonious disputes, none of the secondary national powers is in a position to displace the Americans. The international order, consequently, will evolve from crisis to crisis.